Evaluating the Effectiveness of Islamic Religious Education Learning in Implementing 2013 Curriculum in Madrasah - St. Jumaeda (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
This study aims to obtain objective information, process quality, and output quality in Islamic religious education learning. The present study used a qualitative approach with the model developed by Widoyoko covering the quality of the process and the quality of the learning output. This research applies a program evaluation study method. The data were collected through document studies, interviews, questionnaires, and observations. The results showed that the evaluation of the Islamic Religious Education learning program in Madrasah Aliyah Negeri 1 Central Maluku Regency was in good category (84%) based on the quality of the learning program process and learning output. There are several aspects in evaluating the quality of the process and the quality of learning output that need to be improved. Learning facilities, student motivation, class climate, student attitudes, and students' personal skills should be improved to achieve effective and efficient Islamic religious education learning.